A gestão na micro e pequena empresa sob a ótica do prêmio TOP Empresarial - Castro, Marcus Vinicius Vianna (2005)
The study about micro and small size brazilian companies is highly relevant, because searches understanding the economic situation of the country and its effects, in order to consider the issue of entrepreneurship, which Brazil stands in 7th place worldwide, providing a profile of the Brazilian entrepreneur. The evaluation of the quality management methodology of such companies is a key-factor to create incentives for the entrepreneur and manager, in order to minimize its risks and contribute for reducing the mortality rate, which is considerably high in Brazil. The National Quality Award, through its regional awards focused to micro and small size companies. The case to be studied is an example of which - the Top Enterprise Award for micro and small size companies in Rio de Janeiro. Thus, a survey was developed, aiming evaluating the seven corporate sectors and eight excellence criteria established by the National Quality Award, based on the score of micro and small size companies that were finalists and awarded in the Top Enterprise Award, rounds 2003 and 2004. The result of this survey, in a comparison study between both rounds, indicates evolutions and involutions occurred, from which we can highlight the low performance score in the general criteria of some sectors. Concerning criteria, the survey also shows that the low performance in Strategy & Plans, characteristic in micro and small size companies, and the Society criteria, which obtains the higher levels of evolution and involution